MEETING POINTS AND DIFFERENCES ISLAMIC MULTICULTURALISM AND WESTERN MULTICULTURALISM AS UNIVERSAL HUMAN VALUES - Irham, Irham; Haq, Sansan Ziaul (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2024)
Multiculturalism has become a universal human value that can be accepted from all walks of life. However, the term multiculturalism originated in the West and its development later, Islam, whose early development (since the 6th century) has taught the values of Multiculturalism. This is called Islamic Multiculturalism with its values of justice (al-'ada>lah), equality (al-musa>wa>h), tolerance (al-tasa>muh}), brotherhood of humanity (al-ukhuwwah al-insa>niyyah), universal compassion (al-rah}mah al-'a>mmah). This article is a comparative study of them to find common ground and differences. Islamic Multiculturalism and Western Multiculturalism both teach universal values with the same goals of upholding human dignity and dignity, respecting differences, diversity, and pluralism, and creating world peace—the difference between the two lies in the background of the background. Western Multiculturalism has its roots in a purely socio-cultural movement to abolish social discrimination. Islamic Multiculturalism originates from the normative teachings of the Quran-Hadith and the early history of Islamic development. These two sources can complement and reinforce each other for one universal human value, namely Multiculturalism.